PENERAPAN MANAJEMEN RISIKO PADA PERBANKAN DI INDONESIA - KARTIKA SARI, LISA Kartika (Jurnal Akuntansi AKUNESA, 2012)
This study aims to determine how to manage bank risk management, the advantages, benefits and barriers in implementing risk management in banks and the impact of risk management related to pillars of Indonesia Banking Architecture (API). The method used in this research is descriptive analysis of the qualitative approach. The result shows that, how to manage risk can be done by identifying risks, each risk measure, monitor and control risks. Benefits of riskmanagement is to create a strong banking infrastructure in order to improve the competitiveness of the bank but have constraints on low surveillance systems. The impact of the implementationof risk management have a good effect related to the implementation pillars of indonesia banking architechture so that the structure of banking system healthy, independent and effective supervision, a strong banking industry, and protected consumer. Keywords: API, Benefits, Pillars, Risk Management, Risk Profile.